A STUDY ABOUT DEVELOPING MOBILITY ADRESSED TO CADET ATHLETES THAT PRACTICE TAEKWONDO THROUGH INTRODUCING A TAE-BO PROGRAM - GLEVEȘANU Andreea Eveline (Editura Universitatii Transilvania din Brasov, 2020)
Mobility is an important quality for a Taekwondo practitioner, that's why a high level of mobility is required to increase performance, efficiency and economy of movement. The article highlights a major importance through introducing the Tae Bo program and the benefits it brings in the Taekwondo discipline. The purpose is to identify and check the efficiency of the training method through introducing the Tae Bo program and the beggining of the Taekwondo training. Through the present paper we wish that the results gathered from using the method to prove the improvement of the coxo-femoral mobility.